Consequences of the exposome to gestational diabetes mellitus - Rudge, Marilza V.C. [UNESP]; Alves, Fernanda C.B. [UNESP]; Hallur, Raghavendra L.S. [UNESP]; Oliveira, Rafael G. [UNESP]; Vega, Sofia [UNESP]; Reyes, David R.A. [UNESP]; Floriano, Juliana F. [UNESP]; Prudencio, Caroline B. [UNESP]; Garcia, Gabriela A. [UNESP]; Reis, Fabiana V.D.S. [UNESP]; Emanueli, Costanza; Fuentes, Gonzalo; et al. (Elsevier, 2023)
The exposome is the cumulative measure of environmental influences and associated biological responses throughout the lifespan, including those from the environment, diet, behaviour, and endogenous processes. The exposome concept and the 2030 Agenda for the Sustainable Development Goals (SDGs) from the United Nations are the basis for understanding the aetiology and consequences of non-communicable diseases, including gestational diabetes mellitus (GDM). Pregnancy may be developed in an environment with adverse factors part of the immediate internal medium for fetus development and the external medium to which the pregnant woman is exposed. The placenta is the interface between maternal and fetal compartments and acts as a protective barrier or easing agent to transfer exposome from mother to fetus. Under and over-nutrition in utero, exposure to adverse environmental pollutants such as heavy metals, endocrine-disrupting chemicals, pesticides, drugs, pharmaceuticals, lifestyle, air pollutants, and tobacco smoke plays a determinant role in the development of GDM. This phenomenon is worsened by metabolic stress postnatally, such as obesity which increases the risk of GDM and other diseases. Clinical risk factors for GDM development include its aetiology. It is proposed that knowledge-based interventions to change the potential interdependent ecto-exposome and endo-exposome could avoid the occurrence and consequences of GDM.
Keywords: biomarkers; endogenous exposomes; environmental exposures; exposome; gestational diabetes